Research of pricing processes in the regional markets of autoclaved aerated concrete of Ukraine in 2020 on the basis of cluster analysis - Skrypnyk, O. (Ways to Improve Construction Efficiency, 2022)
The article is devoted to the analysis of the situation of regional aerated concrete markets in Ukraine in 2020 and the processes of pricing on them using cluster analysis. The interrelation of the main indicators of the situation in the regional markets of aerated concrete, taking into account the peculiarities of pricing in an oligopoly, is described. The level of aerated concrete supply in the regional markets of Ukraine is estimated on the basis of data on the territorial location of aerated concrete producers in Ukraine and the directions of their distribution of their products, as well as the volume and territorial distribution of imports. The level of demand for aerated concrete in each region of Ukraine is estimated on the basis of data on regional construction volumes, regional real estate prices and regional price of aerated concrete. The relationship between the supply of aerated concrete in the regions of Ukraine and the level of prices for it, as well as between the demand for aerated concrete in the regions of Ukraine and the level of prices for it. Based on the comparison of the relative levels of regional demand and supply of aerated concrete, the balance of the aerated concrete market in each region of Ukraine is determined. Regional clusters of the aerated concrete market of Ukraine have been formed according to the indicators of the level of aerated concrete prices and the balance of the respective regional market. The expediency of introduction of complex regulation of pricing in the regional markets of aerated concrete of Ukraine by aerated concrete producers and the state is substantiated, and also necessity and possible directions of regulation of prices for aerated concrete for each of the defined clusters are defined.